SISTEM PENDUKUNG KEPUTUSAN SELEKSI PSB BERBASIS WEB MENGGUNAKAN METODE ANALITYC NETWORK PROCESS - Nobi Albion Ziqkra; Yeka Hendriyani (Universitas Negeri Padang, 2019)
New Student Admission Selection is a process in receiving students with structured registration flow (acceptance and selection) by fulfilling the requirements. This system was developed based on Web, using the programming language PHP (Hypertext Processor) and based on Laravel and Mysql Framework as a Database Management System (DBMS). Analystc Network Process (ANP) is one method that has a relationship between elements that can determine the results in the process of selecting new prospective students. In a system developed by the Analysis Process Network method based on Decision Support Systems can help in the process of selecting new students who are supported more accurately. Results that can be obtained from this system for the school that can be accessed in the process of registering and selecting prospective students. Keywords: Decision Support System, PSB Selection, Analysis Network Process (ANP) Method, PHP, Laravel, MySQL.